Literature Review: High Intensity Interval Training Meningkatkan Kebugaran Jasmani dan Sosial Status Pada Orang Dewasa Gaya Hidup Pasif - Daulay, Dio Alif Airlangga; Vigriawan, Gosy Endra; Sidik, Rizky Muhammad; Utami, Try Setyo; Pratama, Henri Gunawan (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
WHO recommendations (2020) advise adults to do moderate intensity physical activity for 150-300 minutes (40-60% of Maximum Heart Rate) or high intensity physical activity for 75-150 minutes (60-85% of Maximum Heart Rate ) ) per week to maintain and improve fitness. However, often obstacles such as "lack of time", low motivation, and non-compliance with existing guidelines are reasons for not exercising. High Intensity Interval Training (HIIT) offers a solution that requires less time but still provides health benefits that are equal or even greater than the physical activity recommendations from WHO. This study aims to determine the effect of HIIT on physical fitness, VO2Max, and social status. The method used is library observation by searching for articles from electronic databases such as PubMed, ScienceDirect, and ProQuest. The research results show that HIIT can improve physical fitness, have a positive effect on social status significantly and efficiently.